Investment in children’s health and well-being: Canadian evidence for two-parent families - Nistor, Simona (Université d'Ottawa | University of Ottawa, 2005)
Using the first cycle (1994-1995) of the National Longitudinal Survey of Children and Youth (NLSCY), I estimate the investment levels of the two-parents families into the health and well-being of their children. Controlling for the household income, size,